Control of a Double Fed Induction Generator Based Wind Energy Conversion System Equipped with a Modular Multilevel Matrix Converter - Rojas-Lobos, F; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2019)
During the last years, the Modular Multilevel Matrix Converter (M3C) has been investigated due to its capacity tooperate in high voltage and power levels. This converter is appropriate for Wind Energy Conversion Systems (WECSs), due to its advantages such as redundancy, high power quality, expandability and control flexibility. For Double-Fed Induction Generator (DFIG) WECSs, the M3C has advantages additional benefits, for instance, high power density in the rotor, with a more compact modular converter, and control of bidirectional reactive power flow. Therefore, this paper presents a WECS composed of a DFIG and an M3C. The modelling and control of this WECS topology are described and analyzed in this paper. Additionally, simulation results are presented to validate the effectiveness of this proposal. © 2019 IEEE.